Analysis of Law Enforcement Patterns Criminal Corruption in Criminal Law Perspective and Eradication Efforts Corruption in Indonesia - T. Ikhsan Ansyari Husny; Yasmirah Mandasari Saragih; Fauzan Fauzan; Muhammad Faiz Hadi; Ayanda Shiro Kamarullah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Corruption is an unlawful act to enrich or obtain one-sided benefits, corruption has rules that have specific characteristics, both regarding formal (procedural) and material (substance) criminal law, law enforcement of corruption in Indonesia depends on the Criminal Justice System itself, from investigation then prosecution, and examination in court and the implementation of the punishment. The formulation of the problem in this study is how the pattern of law enforcement against corruption in the perspective of criminal law in Indonesia, and how efforts and criticism of the eradication of corruption in Indonesia. This research method is descriptive and normative juridical approach, with legal materials as secondary data. relating to law enforcement against criminal acts of corruption in the Indonesian criminal justice system. the criminal justice system in Indonesia is not yet competent in handling criminal acts of corruption because instead of subsidizing, corruption cases in Indonesia are increasing. this is because the four criminal justice systems in Indonesia lack coordination and supervision, and the sanctions given are still considered not optimal so that they have not caused a deterrent effect on the perpetrators and the effect of public satisfaction.